Knowledge of marine mammal professionals on ecosystem services associated with the marine manatee (Trichechus manatus) in Brazil - Bonfietti Izidoro, Flavia; Romero, Renato de Mei; Schiavetti, Alexandre (Ethnobiology and Conservation, 2022)
Ecosystem services are the benefits we derive from the ecosystems we occupy. These services are related to biodiversity and this interaction ensures the functioning of the processes necessary for their own maintenance. The aim of this study was to identify the perception of ecosystem services associated with West Indian manatee (Trichechus manatus) in their sites of occurrence in Brazil. Data collection was carried out using forms completed autonomously by professionals who participated in the elaboration of the National Action Plan for the Conservation of Sirenia in Brazil. Most respondents belong to private institutions and have more than ten years’ experience in these field. We found a positive and significant correlation between pressures and threats in manatees, that currently affect in ecosystem services and are expected to continue in the future. No differences were observed in perception regarding the presence of categories of ecosystem services. Thus, it is considered that researchers believe that all categories were relevant in their geographic area of activity. Finally, we describe particularly some ecosystem services provided by manatee with emphasis in the cultural. The traditional fishing communities were considered the public that most benefited from all services.